Sa ugoy ng duyan - Villanueva, Rene O. ([Manila] Asian Social Institute Communication Center, 1991)
Shows the positive and negative aspects of the family's role in the Filipino value system.
Tagapagsalaysay, Prof. Lucio San Pedro.
Keywords: Family -- Philippines; Filipinos; Sociology